Knowledge and Awareness of Oral Health in Type 2 Diabetes Mellitus Patients Visiting A THQ Hospital in Punjab, Pakistan - Afifa Ehsan, Farhan Riaz, Ali Raza, Ejaz Hussain Sahu, Ehsan Rathore, Umer Abdullah (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Oral complications of diabetes mellitus have an influence on the general health and well-being of the people and demonstrate to be a burden for the dental health sector, predominantly in developing countries. The current study aimed to check the awareness and knowledge of oral health status concerning Type II diabetes mellitus patients at a THQ hospital in Sargodha, Pakistan, and perform an oral examination to evaluate oral health status. Methods: This study was conducted at a THQ hospital in District Sargodha in which 180 Type 2 diabetes mellitus patients were included. Data was documented employing a structured questionnaire which was administered to participants visiting the outpatient department. Results: The average age was documented to be 41.58 ± 8.35 years. It was discerned that 44% of the study participants had adequate oral health awareness; however, 56% had insufficient oral health understanding. The outcomes indicated that 62% had adverse oral health as revealed by their scores on the oral health attitude questionnaire while 38% were noticed to have good oral hygiene. It was also seen that the oral health attitude was strongly correlated with oral health knowledge (P 0.01). Conclusions: The findings of this study signify that Type 2 diabetes mellitus patients visiting district Sargodha have insufficient oral health awareness and reveal undesirable oral health attitudes. Based upon these results, community-oriented oral health promotion programs are essential to steer the lifestyle of diabetic patients.